100-m standoff detection of a QCL-induced photo-vibrational signal on explosives using a laser vibrometer. (August 2018) - Fu, Yu; Liu, Huan; Xie, Jiecheng
Highlights: This manuscript describes a new application of one of key techniques in photomechanics area – laser Doppler vibrometry. In this application, we use a broadband quantum cascade laser as an excitation light source and a home-developed long-distance laser Doppler vibrometer as a sensor for photoacoustic/photothermal spectroscopy on three types of explosives at 100 m standoff distance. Based on our knowledge, this is the first-ever reported detection of photoacoustic signal of trace explosives using optical non-contact interferometric technique at a meaningful safe distance. The results demonstrate that the LDV is a good non-contact sensor for long-distance photo-vibrational signal detection in open environment, compared with other sensors like high sensitivity microphone. It is the second report on our research progress in a series of developments to realize the proposed technology for standoff detection of hazardous materials in defense and security screening applications. Abstract: Laser Doppler vibrometry is a key technology in the field of photomechanics. It allows pointwise noncontact measurements of dynamic effects. In recent years, it has been applied as a sensor in photoacoustic/photothermal spectroscopy to detect hazardous chemicals or explosive substances in an open environment. In photoacoustic spectroscopy, normally the analysis has to be conducted in a sealed space to enable signal detection, either through a high-sensitivity microphone, or a piezo-sensor coupled with a lock-in amplifier. In addition, the requirement for sample preparation prior to analysis is an impediment preventing practical adoption of the technique in real-time, standoff chemical detection deployments in an open environment. The research team has previously demonstrated the feasible use of a laser interferometric technique to detect photo-vibrational signals of trace chemicals because it was excited by an intensity-modulated quantum cascade laser (QCL). In this study, our long distance laser Doppler vibrometer developed in house was demonstrated to be able to detect the vibration amplitude and frequency of trace explosives at long standoff distances of 100 m in an open environment. Three explosives of 10 µg/mm 2 concentration were tested, and the photo-vibrational spectrum obtained by scanning the output wavelength of the QCL through the mid-IR range, coincides well with the corresponding spectrum obtained using typical FTIR equipment. The experiment demonstrated that the detection of hazardous chemicals or explosive substances at a safe standoff distance can be realized through a system utilizing capable interferometric sensors like the laser Doppler vibrometer, coupled with a QCL excitation source.